Analisis Keberlanjutan Perkebunan Kakao Rakyat di Kawasan Perbatasan Pulau Sebatik, Kabupaten Nunukan, Provinsi Kalimantan Timur - Hidayanto, M.; S., Supiandi; Yahya, S.; Amien, L. I. (Jurnal Agro Ekonomi, 2009)
EnglishSebatik Island, Nunukan Regency is one of the border area of Indonesia and Malaysia. Cocoa is the major commodity in this area. The objective of this study is to analyze the index and sustainability status of cocoa in the border area of Sebatik Island. The analysis uses Multi Dimensional Scaling (MDS) method, called RAP-SEBATIK (Rapid Appraisal for Cocoa on Sebatik Island). RAP-SEBATIK was employed to visualize the status of cocoa in Sebatik Island for five evaluation dimensions. This study uses primary and secondary data. The attributes that affect sensitively on the index and sustainability status was approached using the Leverage and Monte Carlo Analysis. The analysis on the five dimensions (ecology, economy, social-cultural, infrastructure and technology, law and institutional) indicate that ecological dimension is less sustainable (46.23%), economical dimension is less sustainable (48.58%), socio-culture dimension is sustainable (75.20%), infrastructure and technology dimension is less sustainable (36.39%) and dimension of law and institutional is less sustainable (40.49%). Out of 53 attributes, there were 17 attributes need to be taken care immediately because of the sensitive affect on the increase of index and sustainability status.IndonesianPulau Sebatik merupakan salah satu kawasan perbatasan negara antara Indonesia dan Malaysia. Di kawasan perbatasan Pulau Sebatik, tanaman kakao merupakan salah satu komoditas unggulan yang telah dibudidayakan sejak tahun 1980-an. Penelitian ini bertujuan untuk menganalisis status keberlanjutan perkebunan kakao rakyat di kawasan tersebut. Metode analisis yang digunakan adalah Multi Dimensional Scaling (MDS) yang disebut RAP-SEBATIK (Rapid Appraisal for Cocoa on Sebatik Island) yang hasilnya dinyatakan dalam bentuk indeks dan status keberlanjutan. Analisis Leverage dan Monte Carlo digunakan untuk mengetahui atribut-atribut yang sensitif terhadap indeks, dan status keberlanjutan. Hasil penelitian menunjukkan bahwa pada dimensi ekologi statusnya kurang berkelanjutan (46,23%), dimensi ekonomi kurang berkelanjutan (48,58%), dimensi sosial budaya berkelanjutan (75,20%), dimensi infrastruktur dan teknologi kurang berkelanjutan (36.39%) dan dimensi hukum dan kelembagaan kurang berkelanjutan (40,49%). Dari 53 atribut yang dianalisis, terdapat 17 faktor atau atribut yang sensitif terhadap indeks dan status keberlanjutan, sehingga perlu dilakukan upaya perbaikan atau intervensi terhadap atribut-atribut tersebut untuk meningkatkan indeks dan status keberlanjutan.